Kepastian Hukum Pembatalan Perkawinan Kedua akibat Tidak Terpenuhinya Syarat Perkawinan - Fajri, Maulana; Chandra, Tofik Yanuar; Martanti, Yurisa (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Discussion on the legal certainty of the annulment of a second marriage due to the failure to fulfill the marriage requirements. The method used in this study is a normative juridical research type, namely library legal research or secondary data with primary, secondary and tertiary legal sources. The legal certainty of a second marriage according to the Marriage Law that does not fulfill the requirements reflects the failure of the legal norm system to be enforced consistently in accordance with the applicable normative hierarchy, thus giving rise to legal uncertainty. However, even though the marriage is null and void by law, the legal system still provides corrective space through other norms in family civil law that function to maintain the values ​​of justice and humanity. This reflects that legal certainty according to Kelsen is not merely rigid, but also considers corrective mechanisms to protect the basic rights of citizens within the applicable positive legal framework.